2016
DOI: 10.1179/2042618615y.0000000004
|View full text |Cite
|
Sign up to set email alerts
|

Dry needling of the trapezius muscle in office workers with neck pain: a randomized clinical trial

Abstract: Background: Neck pain is a frequent complaint in office workers. This pain can be caused by myofascial trigger points (MTrPs) in the trapezius muscle. This study aimed to determine the effectiveness of deep dry needling (DDN) of active MTrPs in the trapezius muscle. Methods: A randomized, single blinded clinical trial was carried out at the Physical Therapy Department at Physiotherapy in Women's Health Research Group at Physical Therapy Department of University of Alcalá, in Alcalá de Henares, Madrid, Spain. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 48 publications
5
36
0
7
Order By: Relevance
“…Thus, TrPDNdi.e. without injectatedis becoming a popular therapeutic intervention among health professionals (Rodriguez-Mansilla et al, 2016) and involves the insertion of thin monofilament (Cerezo-Tellez et al, 2016a) or hollow bore needles (Kamanli et al, 2005) without delivery of any drug into a MTrP region. Current systematic reviews report that direct MTrP needling is superior only to placebo for reducing pain (Tough and White, 2011) at immediate (Kietrys et al, 2013), shortterm (Boyles et al, 2015;Kietrys et al, 2013;Liu et al, 2015) and medium-term (Liu et al, 2015) follow up.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, TrPDNdi.e. without injectatedis becoming a popular therapeutic intervention among health professionals (Rodriguez-Mansilla et al, 2016) and involves the insertion of thin monofilament (Cerezo-Tellez et al, 2016a) or hollow bore needles (Kamanli et al, 2005) without delivery of any drug into a MTrP region. Current systematic reviews report that direct MTrP needling is superior only to placebo for reducing pain (Tough and White, 2011) at immediate (Kietrys et al, 2013), shortterm (Boyles et al, 2015;Kietrys et al, 2013;Liu et al, 2015) and medium-term (Liu et al, 2015) follow up.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, dry needling also appears to be associated with activation of diffuse noxious inhibitory control reducing pain sensitivity in remote areas to the site of needling. This may be mediated through endogenous opioid mechanisms [ There are a number of papers in support of the treatment effects, beyond the placebo effect, of myofascial release [51,62,66,[87][88][89][90][91][92][93][94][95][96][97][98][99]. Recent reviews have concluded that better quality studies with standardized interventions and outcomes are required to show that myofascial release is an effective intervention in the different types of myofascial pain syndromes [100][101][102].…”
Section: Muscle Activationmentioning
confidence: 99%
“…Skausmo slenksčiui matuoti pasirinkta algometrija ir naudojamas skaitmeninis "Wagner Instruments" algometras. Matuojant skausmo slenkstį, tiriamieji turėjo pasakyti "stop" tuomet, kai pajausdavo diskomfortą ar skausmą spaudimo vietoje (Cerezo-Tellez et al, 2016). Buvo tirti kairės ir dešinės pusės raumenys (1 pav.…”
Section: Metodaiunclassified